Sustaining environment through natural resource and human development: Revisiting EKC curve in China through BARDL - Long, Hai; Li, Wen-Wei; Otrakçı, Caner (Resources policy, 2023)
Addressing environmental degradation is a critical global challenge, yet nowhere is this more pressing than in China, given its unique economic and environmental landscape. Prior research has highlighted the profound imbalance between the nation's escalating energy demands and limited supplies, exacerbating China's environmental predicament and threatening its sustainable growth potential. This study, therefore, endeavors to scrutinize the dynamic interplay between natural resources (NTR), human development (HMD), and economic growth (GDP), with a specific emphasis on their collective impact on environmental pollution. Utilizing a Bootstrapped ARDL approach on data collected from various sectors over the last two decades, we explore the distinct roles these factors play. Our findings reveal a positive relationship between NTR and CO2 emissions, indicating that NTR inadvertently contributes to pollution increase. Conversely, we discern a negative relationship between HMD and CO2 emissions, implying that advances in human development can effectively counteract pollution. The implication of these findings is profound, suggesting that careful management of natural resources, alongside investment in human development, could present a viable path towards sustainable growth. These insights can guide corporations and policymakers in designing strategies that reconcile economic progress with environmental stewardship. •The study focuses on pollution in China, a pressing topic for economic and environmental studies.•Energy supply-demand imbalance & deteriorating environmental conditions threaten China's sustainable growth.•The research analyzes the roles of natural resources, human development, and economic growth in reducing pollution.•NTR complements CO2 emissions while HMD mitigates them.•Findings call for strategies addressing NTR and HMD to reduce pollution, guided by policymakers and companies.